Bis-Thiourea bearing aryl and amino acids side Chains and their antibacterial activities - Wan Sharifatun Handayani, Wan Zullkiplee; Ainaa Nadiah, Abd Halim; Zainab, Ngaini; Maya Asyikin, Mohd Ariff; Hasnain, Hussain (Taylor & Francis Group, LLC, 2016)
A series of symmetrical 1,3-bis thiourea 1a–e and 1,4-bis thiourea derivatives 2a–e have been successfully synthesized from the reactions of amines with 3-acetylbenzoyl isothiocyanate and 4-acetylbenzoyl isothiocyanate, respectively. All the synthesized compounds were characterized by FT-IR spectroscopy and 1H and 13C NMR spectroscopy. The compounds were screened for their antibacterial activity by turbidimetric method using gram-negative bacteria (E. coli ATCC 8739) using turbidimetric method. The newly synthesized bis-thiourea derivatives bearing aryl side chains showed good antibacterial activity against E. coli. The effect of the molecular structure of the synthesized compounds on the antibacterial activity is discussed.